If a , b , and c are real numbers greater than − 1 and
1 + b + 1 + c = 2 1 + a ,
then b + c ≥ 2 a .
The statement above is always true or false?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Brilliant solution! Just develop an equation between b,c and a and then plug in.
Here is my solution: 1 + b + 1 + c = 2 1 + a ⇒ ( 1 + b + 1 + c ) 2 = 4 ( 1 + a )
Next, we use the inequality ( a + b ) 2 ≤ 2 ( a 2 + b 2 ) .
⇒ ( 1 + b + 1 + c ) 2 = 4 ( 1 + a ) ≤ 2 ( 2 + c + b ) ⇔ 2 a ≤ c + b
Let x = 1 + a , y = 1 + b , and z = 1 + c . Then a = x 2 − 1 , b = y 2 − 1 , and c = z 2 − 1 .
Substituting these values into the given equation 1 + b + 1 + c = 2 1 + a gives y + z = 2 x , so x = 2 y + z .
Substituting these values into the given inequality b + c ≥ 2 a gives ( y 2 − 1 ) + ( z 2 − 1 ) ≥ 2 ( x 2 − 1 ) , which simplifies to y 2 + z 2 ≥ 2 x 2 , and substituting x = 2 y + z into this gives y 2 + z 2 ≥ 2 ( 2 y + z ) 2 which rearranges to ( y − z ) 2 ≥ 0 , which is always true for real numbers y and z .
I tought it was false, because when you choose for example -6 for b then it's a root of a negative number.
Log in to reply
Yes, you have to assume that 1 + a , 1 + b , and 1 + c are real numbers (which probably should have been stated in the problem), otherwise one counterexample is a = − 4 9 , b = − 6 , and c = − 1 .
Log in to reply
Yes, I didn't assume that, so that was the problem. Thanks for your explanation.
Consider the function f ( x ) = 1 + x . The statement given is equivalent to
2 f ( b ) + f ( c ) = f ( a ) . We are asked whether this implies that 2 b + c ≥ a .
Clearly this is true for the trivial case when a = b = c . Let us assume b = c .
Some things to consider about f ( x ) = ( 1 + x ) 2 1
Its domain is [ − 1 , ∞ )
Its first derivative is f ′ ( x ) = 2 1 ( 1 + x ) 2 − 1 and f ′ ( x ) > 0 , for all x ∈ ( − 1 , ∞ ) . Thus f ( x ) is an increasing function.
In particular, for b = c ,
2 f ( b ) + f ( c ) < f ( 2 b + c ) . Thus f ( a ) < f ( 2 b + c ) .
Since f ( x ) is an increasing function over its entire domain, the latter fact implies that a < 2 b + c . QED
I write a python program to vividly showing the function and the relationship between a,b,c
import numpy as np
import matplotlib.pyplot as plt
import math
xLine = np.linspace(-1, 5, num=200)
y = np.array([ math.pow(item+1, 0.5) for item in xLine])
plt.plot(xLine,y,label='y = (x+1)^0.5')
plt.plot(xLine,xLine , label='y = x' )
plt.plot([-1, 1], [0, 2**0.5], 'ro', label= 'b,c')
plt.plot([-1/2], [0.5**0.5], 'go', label='a')
plt.legend()
plt.grid()
plt.xlabel('x')
plt.show()
y = (1+x)^0.5 is a Convex function, so the inequality is always true
Problem Loading...
Note Loading...
Set Loading...
If we square both sides of the original radical equation, we obtain:
( 1 + b ) + ( 1 + c ) + 2 ( 1 + b ) ( 1 + c ) = 4 ( 1 + a ) ⇒ 2 b + c − 2 + 2 ( 1 + b ) ( 1 + c ) = 2 a (i)
Substituting (i) into the RHS of desired inequality above now yields:
b + c ≥ 2 b + c − 2 + 2 ( 1 + b ) ( 1 + c ) ;
or 2 b + c + 1 ≥ ( 1 + b ) ( 1 + c ) ;
or b + c + 2 ≥ 2 ( 1 + b ) ( 1 + c ) ;
or ( b + c ) 2 + 4 ( b + c ) + 4 ≥ 4 ( 1 + b ) ( 1 + c ) ;
or b 2 + 2 b c + c 2 + 4 b + 4 c + 4 ≥ 4 + 4 b + 4 c + 4 b c ;
or b 2 − 2 b c + c 2 ≥ 0 ;
or ( b − c ) 2 ≥ 0
which is TRUE for all choices of b , c ∈ R .